Gestão de membresia: a relação entre associação e associados em três casos brasileiros - Nogueira, Fernando do Amaral (2014)
The objective of this thesis is to investigate what membership management practices voluntary associations conduct to attract, engage and maintain members. This key feature in the management of this type of organization has had so far little attention in the existing literature, which tends to focus more on the democratic effects of participating in associations. The theoretical lens to analyze the practices comes from Organizational Theory, in particular the Institutional Work approach. The aim is to understand whether the membership management contributes to the institutionalization of associations. Three case studies focusing on different Brazilian associations were conducted: The Brazilian Institute of Criminal Sciences (IBCCrim), the Brazilian Association of Non-Governmental Organizations (Abong) and the Brazilian Institute of Corporate Governance (IBGC). The analysis focused on the following questions: what are the membership management practices designed to recruit, retain and engage members? How can these practices have institutionalizing effects? Who is involved with membership management? What are the variations depending on the kind of member – individual (IBCCrim), organizational (Abong) or mixed (IBGC)? The cases show how dozens of identified practices are performed not only by managers, but also by board members, the professional and voluntary staff and members in general. It was also observed how these practices are related to different types of institutional work, especially those linked to normative and cognitive-cultural aspects: building and strengthening identity, defining boundaries, editing and telling narratives, institutional leadership and infusion of values and creation of routines. This ultimately shows how the relationship between association and associate can go far beyond an utilitarian exchange of goods and services. The main contributions of the study include: showing the potential of using an Institutional Theory lens to understand associations; shedding light on one aspect of management association – membership management – that deserves more studies in Brazil and abroad; and increasing our understanding of meta-organizations, associations of a special type, whose members are other organizations.